Excitatory and inhibitory projections in parallel pathways from the inferior colliculus to the auditory thalamus - Jeffrey Garrett Mellott; Nichole L Foster; Nichole L Foster; Andrew P Ohl; Brett R Schofield; Brett R Schofield (Frontiers Media S.A., 2014)
Individual subdivisions of the medial geniculate body (MG) receive a majority of their ascending inputs from 1 or 2 subdivisions of the inferior colliculus (IC). This establishes parallel pathways that provide a model for understanding auditory projections from the IC through the MG and on to auditory cortex. A striking discovery about the tectothalamic circuit was identification of a substantial GABAergic component. Whether GABAergic projections match the parallel pathway organization has not been examined. We asked whether the parallel pathway concept is reflected in guinea pig tectothalamic pathways and to what degree GABAergic cells contribute to each pathway. We deposited retrograde tracers into individual MG subdivisions (ventral, MGv; medial, MGm; dorsal, MGd; suprageniculate, MGsg) to label tectothalamic cells and used immunochemistry to identify GABAergic cells. The MGv receives most of its IC input (~75%) from the IC central nucleus (ICc); MGd and MGsg receive most of their input (~70%) from IC dorsal cortex (ICd); and MGm receives substantial input from both ICc (~40%) and IC lateral cortex (~40%). Each MG subdivision receives additional input (up to 32%) from non-dominant IC subdivisions, suggesting cross-talk between the pathways. The proportion of GABAergic cells in each pathway depended on the MG subdivision. GABAergic cells formed ~20% of IC inputs to MGv or MGm, ~11% of inputs to MGd, and 4% of inputs to MGsg. Thus, non-GABAergic (i.e., glutamatergic) cells are most numerous in each pathway with GABAergic cells contributing to different extents. Despite smaller numbers of GABAergic cells, their distributions across IC subdivisions mimicked the parallel pathways. Projections outside the dominant pathways suggest opportunities for excitatory and inhibitory crosstalk. The results demonstrate parallel tectothalamic pathways in guinea pigs and suggest numerous opportunities for excitatory and inhibitory interactions within and between pathways.